Lilium punctulatum (Liliaceae), a rare and endangered species from northwestern Yunnan, China, elevated from varietal to species status - Yuan, Yumei; Ju, Wen-Bin; Gao, Yundong (Phytotaxa, 2022)
Lilium punctulatum, a taxon endemic to northwestern Yunnan, used to be considered a form of Lilium pardanthinum. It is here investigated and proposed for species rank. Morphologically, it is closest to L. basilissum and L. sealyi, but it can be differentiated by its dark red spots on pinkish petals, inner tepals margin shallowly erose or lacerate, elliptic to lanceolate-elliptic leaves and a saucer-shape perigone. This species has a narrow distribution and small population size, which makes it vulnerable to extinction, and thus it needs urgent conservation attention.